"Digitalizing Walkability": Comparing Smartphone-Based and Web-Based Approaches to Measuring Neighborhood Walkability in Singapore. Issue 3 (3rd July 2019) - Yun, Hae Young; Zegras, Christopher; Palencia Arreola, Daniel Heriberto
ABSTRACT: We evaluated two digitally enabled approaches to measuring neighborhood walkability: a smartphone-based, on-site pedestrian environmental audit tool, WalkTracker ( WTracker ), and remote, Web-based (Web) observations. Specifically, we examined street segments and intersections of a neighborhood in Singapore assessing: (1) the Inter-Rater Reliability (IRR) of each approach; (2) the Inter-Method Reliability (IMR) across the two approaches; and (3) the average observation times of the two approaches. Each approach had high IRR for the land use and traffic-related domains, with the Web performing better than WTracker for land use. In these same two domains, the two tools were relatively consistent (high IMR), although higher agreement was found within the tools than across them (IRR higher than IMR). For subjective or fine-grained features, both approaches had low IRR, with the Web-based approach performing worse than the app-based approach. Performance across the instruments was also worse than the reliability of measurements within each instrument (IMR lower than IRR). Some items were not observable via the Web. In terms of observation time, there was no statistically significant time difference in measurements between the two observation methods, not including the round-trip travel time to the site. A hybrid approach, combining the two approaches, might be most appropriate.